Pengelolaan Keuangan Masjid Berbasis Manajemen Keuangan Syariah - Nabila Tasya Nurhafifah Manurung; Chuzaimah Batubara (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2025)
Management-based mosque financial management is an organized and structured approach in managing mosque financial resources effectively and efficiently. This abstract will discuss the importance of good financial management in the context of mosque management, as well as how the application of management principles can improve the financial performance of mosques.This abstract outlines several important aspects of mosque financial management. First, it explains why good financial management is so important for the sustainability and development of mosques. In this context, a mosque is a religious institution that requires funds to meet operational, maintenance, and development projects. Then, this abstract examines relevant management concepts in mosque financial management. This includes setting budgets, cash management, accounting, financial reporting, and oversight. In managing financial mosques, it is important to have a clear budget plan, monitor receipts and expenditures carefully, and report finances transparently to congregations and related parties. Furthermore, this abstract discusses the importance of applying good management principles in mosque financial management. These principles include managing risk, developing sources of income, managing assets, and developing financial policies. By implementing these principles, mosques can optimize the use of available financial resources, reduce financial risks, and ensure long-term growth. Finally, this abstract underscores the importance of effective leadership in mosque financial management.